Experimental observations of chimera states in locally and non-locally coupled Stuart-Landau oscillator circuits. (September 2020) - Gambuzza, L.V.; Minati, L.; Frasca, M.
Highlights: Design of an experimental setup for the investigation of spatio-temporal dynamical patterns in coupled Stuart-Landau oscillators. Analysis and characterization of the spatio-temporal dynamical patterns occurring both in local and non-local ring configurations. Consistent observations of amplitude chimera states, showing their reproducibility, stability and robustness to heterogeneities in real experiments. Abstract: Nontrivial spatiotemporal patterns emerge across many systems of interacting oscillators, still the number of experimental investigations remains relatively limited. In this paper, we consider an experimental setup of ten electronic circuits, each of which modeling a Stuart-Landau oscillator, and investigate different arrangements of their interactions under diverse settings of the coupling strength, which acts as a bifurcation parameter for the system. We introduce a set of three empirical measures, allowing the straightforward classification of synchronization states in this system. We observe a rich repertoire of synchronization patterns, including global synchronization, oscillation death, chimera states and traveling waves, spontaneously breaking the symmetry of the configuration. Interestingly, the intervals of the bifurcation parameter wherein these states are observed overlap, revealing multiple regions of multistability. Our experimental results also allow drawing important conclusions on the chimera states observed, showing that i) they can be consistently observed in a system of relatively low size, ii) they are stable, iii) their basin of attraction is large enough to encompass the 'normal' operating conditions of the circuit, iv) their emergence is not appreciably influenced by small heterogeneities between units due to parametric tolerances.